PENINGKATAN MOTIVASI DAN PRESTASI BELAJAR PPKN MATERI SISTEM PEMERINTAHAN DESA DAN KECAMATAN MELALUI METODE DISKUSI PADA SISWA KELAS IV SDN KARANGSAMBIGALIH II KECAMATAN SUGIO KABUPATEN LAMONGAN - Shodikin Shodikin (MEDIA DIDAKTIKA, 2022)
This study aims to describe the increase in Civics learning outcomes using the discussion method in class IV students at SDN Karangsambigalih II, Sugio District, Lamongan Regency. This type of research is classroom action research. The research subjects were fourth grade students at SDN Karangsambigalih II, Sugio District, Lamongan Regency, totaling 14 students. Data collection methods in this study used tests, observation and documentation. Research instruments in the form of tests and observation sheets. The data analysis technique used is descriptive quantitative and qualitative. The indicator of the success of the action is marked by ≥75% of the number of students participating in the learning process who have obtained a value of ≥70. The results of the study showed an increase in Civics learning outcomes for fourth grade students at SDN Karangsambigalih II, Sugio District, Lamongan Regency for the 2018/2019 academic year after using the discussion method. In the pre-cycle, students who scored ≥70 by 28.58% increased to 42.85% in cycle I and increased again to 78.57% in cycle II. The average value of learning outcomes in the pre-cycle 58.57 increased to 68.57 and in the second cycle increased to 75.71.